용융탄산염 연료전지용 디젤의 수소첨가탈황 - 김민수; 김현구; 장성철; 김영천; 최선희; 윤성필; 한종희; 남석우; 최대기; 함형철 (한국수소및신에너지학회, 2015)
Hydrogen production from commercial diesel fuels is an attactive option for energy generation purposedue to the low cost and good availability of diesel fuels. However, in order to utilize commercial diesel fuels,the sulfur contents must be removed down to approximately 0.1 ppm level to protect the fuel cell catalysts frompoisoning. Commercial catalysts CoMo/Al2O3 and NiMo/Al2O3 were tested for HDS (Hydrodesulfurization) of modeldiesel and commercial diesel. The experimental conditions were 250 ？ 400 °C and LHSV (Liquid Hourly SpaceVelocity) 0.27 ？ 2.12 hr-1. NiMo/Al2O3 was found to be more effective than CoMo/Al2O3 in removing sulfur frommodel diesel. Based on the experimental results of model diesel, commercial diesel fuel purchased from a localpetrol station was tested for HDS using NiMo/Al2O3. The GC-SCD (Gas Chromatography Sulfur ChemiluminescenceDetector) results showed that the DMDBT (Dimethyldibenzothiophene) derivatives were fully removed from thecommercial diesel fuel proving that HDS with NiMo/Al2O3 is technically feasible for industrial applications.